Analysis of Purchase Decision Estimates Based on Store Atmosphere and Affordable Prices - Kasmad, Kasmad (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2022)
There are many ways to satisfy consumers, including providing a comfortable store atmosphere and affordable prices. Of course, these two strategies are commonplace that must be carried out by modern retail business actors. This research is a form of scientific study, which examines the various possibilities of increasing purchasing decisions. The survey method was chosen, in order to get a direct picture of the consumer. Data were collected through questionnaires, which were conducted incidentally to 98 modern retail consumers. The results of the study explain that a good store atmosphere can increase the feeling of comfort, resulting in an increase in purchases. Likewise with competitive prices, can make consumers interested in buying in stores, compared to other places. In simultaneous results, an estimated value of 87% is obtained, this value explains the magnitude of the opportunity for purchasing decisions to increase if the store conditions are pleasant for shopping, and the prices offered for each product are relatively affordable.